Art in school: objectification and freedom (Revista Educação, Artes e Inclusão, 2021)
This article aims to understand to what extent the objectifications or artistic works produced by students in the classroom, are art, or are only academic exercises without aesthetic value. We use two central approaches to analyze the present object. The first is how the expansion of a esthetic references present in art history, local, regional and universal, are essential for the development of students' artistic production. Without these references, productions will be bound by common sense. The second focus is the freedom of artistic creation, however, not a freedom generated by the student's abandonment of himself, but a free, personal and at the same time collective poetic creation, planned and guided by art teachers. For the analysis we used some empirical information raised in the internship observations of students of the Degree in Visual Arts at UFMS, carried out between 2017 and 2019 and, mainly, theoretical reflections on free aesthetic objectification as antagonistic to repetitive, alienating pseudoartistic activities. We are based on the work of several authors, from the same philosophical perspective, who use the concepts of objectification, freedom, human activity and the dialectical relationship between thesingular and the universal, in education and aesthetics.
Keywords: arts teaching; creativity; aesthetic appropriation; dialectic